Evaluation of psychosocial, somatosensory and behavioral profiles of patients with chronic temporomandibular pain - Quevedo, Henrique Müller de (2020)
Several factors have been evaluated to characterize patterns of normality in healthy individuals and relevant variations in patients with chronic temporomandibular disorders (TMD), for a more accurate diagnosis and personalized treatment. Some variables that have been associated with this type of analysis are psychosocial questionnaires, psychophysical tests, endogenous pain modulation capacity, and the practice of physical activity. The objective of this study is to investigate the inhibitory effects of endogenous pain modulation in healthy subjects and a population with chronic TMD pain and its relationship with associated factors such as psychosocial and somatosensory profiles, as well as physical activity levels. 311 healthy individuals and 68 chronic TMD pain patients aged between 18 and 50 years were included in this study. Questionnaires were applied for psychosocial assessment and provided information on state-trait anxiety (STAI), pain catastrophizing (PCS), quality of sleep (PITTSBURGH), level of physical activity (IPAQ), lifestyle quality (FLC). The somatosensory evaluation was performed on the anterior temporalis muscle of the dominant side of the healthy individuals, and on the side of the reported pain for the chronic TMD pain patients. The following somatosensory test were performed: mechanical pain threshold (MPT), temporal summation (WUR), pressure pain threshold (PPT), and the conditioned pain modulation test (CPM). The Chi-square test was used to identify possible associations between the categorical variables of the study (on a nominal or ordinal scale), comparisons among categories of Physical activity level were made by the Kruskal-Wallis test, followed by Mann-Whitney with Bonferroni correction. A logistic regression was made to evaluate the binary categories of presence of chronic pain and pain modulation capability (assuming a -10% cutoff). All statistical inferences were performed considering a significance level of 5%. Chronic TMD pain patients presented higher values for anxiety traits (p=0,008), catastrophizing (p<0,001) and Pittsburgh scores (p=0,002) as well as lower mechanical (p=0,012) and pressure pain thresholds (p<0,001), and reported a lower lifestyle quality (p<0,001) than healthy individuals. Somatosensory evaluation revealed lower pain thresholds (MPT, PPT) for individuals with chronic pain. Similar values for pain modulation were found when comparing healthy and chronic TMD pain patients and different levels of physical activity did not seem to alter pain modulation levels, but may seem to have a positive effect on anxiety levels, sleep quality, and lifestyle quality. Higher levels of anxiety, catastrophizing, and worse sleep and lifestyle quality were associated with the chronic pain group. Somatosensory evaluation revealed lower pain thresholds for individuals with chronic pain.